Patriarchal Names in Context - Alan Millard (Tyndale Bulletin)
Observing similarities between some Amorite and Patriarchal names, scholars suggested that they indicated that the patriarchal narratives themselves reflect the Middle Bronze Age. Others observed names of the same form were current in later times, so could not point to any specific period for the Patriarchs’ life setting. Further study of Amorite names can strengthen the case for the early date for the Patriarchal names.